Armenian contributions portrayed in 'A Photographic Journey, Oct. 3 - Uribes, Tom::::::::: (2013)
The research project 'American Armenian Contributions to Humanity after the Armenian Genocide and The Armenian World: A Photographic Journey,' by Stepan Partamian will be presented.